PERDAGANGAN MANUSIA DALAM NOVEL SOLD KARYA PATRICIA MCCORMICK - RENYAAN, VALENTINO MAGELHAENS (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This research which is entitled â€œPerdagangan Manusia dalam novel Sold karya Patricia McCormick.â€ focuses on the theme of the novel that describes about human trafficking. The writer chooses this interesting novel as this novel is one of the McCormickâ€™s works which becomes a National Book Award finalist. The purpose of this study is to identify and categorize the types of human trafficking depicted in the novel. Through this research, the community is expected to know the types of human trafficking and can avoid becoming a victim of human trafficking. The writer uses the intrinsic approach to gain understanding through the plot of the novel and the extrinsic approach to analyze the novel that from social perspective. This research uses the theory from Wellek and Warren (1949), in their book, The Theory of Literature. According to them, literary works are social documents, which reflect a picture of social reality. The result of this research shows that there are many types of human trafficking, reflected through the plot and characters of the novel. Those types are Bonded Labor, Debt Bondage Among Migrant Laborers, Forced Labor, Forced Child Labor, Sex Trafficking, Child Sex Trafficking. Â  Keywords : Novel, Plot, Human Trafficking, Patricia McCormick